Accelerating the spread of laboratory quality improvement efforts in Botswana - Kelebeletse O. Mokobela; Mpho T. Moatshe; Mosetsanagape Modukanele (AOSIS, 2014)
Background: In 2002, the Ministry of Health (MoH) of Botswana began its journey toward laboratory accreditation in an effort to enhance the quality of laboratory services. Aftera difficult start, the MoH recognised the need for a more practical and sustainable method for change that could be implemented nationally; they therefore adopted the Strengthening Laboratory Management Toward Accreditation (SLMTA) programme. Objective: This study describes the spread of laboratory quality improvement efforts in Botswana. Methods: Eight laboratories were enrolled into the SLMTA programme in 2010, which included a series of workshops and improvement projects conducted over nine months. Four of these laboratories received supplementary training and focused mentorship from the Botswana Bureau of Standards (BOBS). Laboratory performance was measured at baseline and exit using the World Health Organization Regional Office for Africa's StepwiseLaboratory Quality Improvement Process Towards Accreditation (SLIPTA) checklist. One laboratory did not receive an exit audit and was thus excluded from the analysis. Results: An 18 percentage-point improvement was observed when comparing the median baseline score (53%) to the median exit score (71%) for the seven laboratories. Laboratories that received additional training and mentorship from BOBS improved 21 percentage points, whilst non-BOBS-mentored laboratories improved eight percentage points. Hospital management buy-in and strong laboratory staff camaraderie were found to be essential forthe positive changes observed. Conclusion: SLMTA facilitated improvements in laboratory quality management systems,yielding immediate and measurable results. This study suggests that pairing the SLMTA programme with additional training and mentorship activities may lead to further increases in laboratory performance; and that SLMTA is a practical approach to extending quality improvement to MOH laboratories.